Endoscopic submucosal dissection in colorectal neoplasia performed with a waterjet system-assisted knife: higher resection rate than conventional technique - Paolo Cecinato; Matteo Lucarini; Francesco Azzolini; Mariachiara Campanale; Fabio Bassi; Annalisa Cippitelli; Romano Sassatelli (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims Colorectal endoscopic submucosal dissection (ESD) is burdened by its associated high risk of adverse events and long procedure time. Recently, a waterjet-assisted knife was introduced to simplify and speed up the procedure. The aim of this study was to evaluate the efficacy and safety of waterjet-assisted ESD (WESD) compared to that of the conventional ESD (CESD) technique. Methods The charts of 254 consecutive patients who underwent colorectal ESD between January 2014 and February 2021 for colorectal neoplasms were analyzed. The primary outcome was the en-bloc resection rate. Secondary outcomes were complete and curative resection rates, the need to switch to a hybrid ESD, procedure speed, the adverse event rates, and the recurrence rates. Results Approximately 174 neoplasias were considered, of which, 123 were removed by WESD and 51 by CESD. The en-bloc resection rate was higher in the WESD group (94.3% vs. 84.3%). Complete resection rates and curative resection rates were similar. The need to switch to a hybrid ESD was greater during CESD (39.2% vs. 13.8%). Procedure speed and adverse event rates were similar. During follow-up, one recurrence occurred after a WESD. Conclusions WESD allows a high rate of en-bloc resections and less frequently requires a rescue switch to the hybrid ESD compared to CESD.